Studi Komparatif Dampak Financial Management Knowledge terhadap Financial Management Behavior Masyarakat Muslim pada Wilayah Urban dan Rural - Adhelia Desi Prawestri (Department of Islamic Banking, Faculty of Islamic Economics and Business, UIN KH Abdurrahman Wahid Pekalongan, 2022)
The Covid-19 pandemic has made people aware that having good financial management knowledge and financial manajemen behavior will help people face times of financial difficulty. Financial decisions take by individuals in society do not only affect each individual, but can also affect the business organization they own. This article aims to determine the relationship between financial management knowledge and financial management behavior in urban and rural Moslem communities. In addition, this article also aims to find out whether there are differences between financial management behavior in Moslem communities living in urban and rural areas. The data used in this study is primary data collected trough questionnaire distributed to 600 samples, namely 300 samples of people in urban areas, and 300 samples of people in rural area, which were collected using convenience sampling technique. A descriptive quantitative approach was used to answer the research questions. The results showed that there was a relationship between financial management knowledge and financial management behavior, and there was no difference between the financial management behavior of Moslem communities living in urban and rural areas.